Role of Prestroke Vascular Pathology in Long-Term Prognosis After Stroke: The Rotterdam Study. Issue 1 (January 2016) - Portegies, Marileen L.P.; Bos, Michiel J.; Hofman, Albert; Heeringa, Jan; Franco, Oscar H.; Koudstaal, Peter J.; Ikram, M. Arfan
Abstract : Background and Purpose—: Mortality after stroke remains high for years, mostly because of cardiovascular causes. Given that cardiovascular pathology plays an important role in causing the initial stroke, such prestroke pathology might also influence the prognosis after stroke. Within the population-based Rotterdam Study, we examined the proportion of deaths after stroke that are attributable to pre-existent cardiovascular risk factors before stroke (the population attributable risk). Methods—: We examined 1237 patients with first-ever stroke and 4928 stroke-free participants (between 1990 and 2012), matched on age, sex, examination round, and stroke date (index date). Cardiovascular risk factors measured on ≈4 years before index date were used as determinants. Participants were continuously followed up for mortality (≈6 years) after the index date. We calculated separate and combined population attributable risk of hypertension, total cholesterol, high-density lipoprotein-cholesterol, body mass index, diabetes mellitus, smoking, transient ischemic attack, and atrial fibrillation. Results—: Nine hundred and nineteen patients with stroke and 2654 stroke-free participants died. The combined population attributable risk in patients with stroke was 27% (95% confidence interval, 14%–45%) and in stroke-free participants was 19% (95% confidence interval, 12%–29%). Population attributable risks of diabetes mellitus, smoking, and atrial fibrillation were higher in patients with stroke than in the reference group because of a higher prevalence of risk factors. In addition, people with atrial fibrillation and stroke had a higher hazard ratio for death than those with only atrial fibrillation. Conclusions—: One quarter of deaths after stroke could theoretically be prevented with rigorous cardiovascular prevention and treatment, but this should preferably start before stroke occurrence. In addition, research into factors explaining the remaining deaths needs to be encouraged. Abstract : Supplemental Digital Content is available in the text.